Consent and mutuality in sex education. Issue 5 (23rd August 2022) - Hand, Michael
Abstract: Sharon Lamb, Sam Gable and Doret de Ruyter have recently argued that sex education in schools should promote a more demanding standard for morally permissible sex than consent. On their view, pupils should be taught that morally permissible sex is not only consensual but also mutual, where mutuality requires participants in sex to 'try to know what is knowable' about each other. I argue here that, while Lamb et al. are right about the insufficiency of consent, the case for mutuality as a standard of moral permissibility cannot be sustained. Mutuality fares better as a standard of moral desirability, but even in this weaker form, it is too controversial to promote in schools.